Maternal presentation and neonatal outcome in peripartum enterovirus infection. (9th December 2020) - Belov, Yekaterina; Many, Ariel; Givon, Ido; Marom, Ronella; Yogev, Yariv; Halutz, Ora; Fouks, Yuval
Abstract: Aim: Enterovirus is a common pathogen. Although mostly asymptomatic, this infection has the potential to be life‐threatening in neonates. This article aims to describe the early neonatal outcomes in peripartum infection. Methods: We performed a retrospective cohort study in a tertiary hospital between 1/2014 and 5/2019. The enterovirus infection was established by real‐time polymerase chain reaction analysis. Results: Out of 161 neonates tested for the enterovirus infection 13 (8%) were positive. Maternal fever was the most common sign ( n  = 8, 66.7%). The mean gestational age at delivery was 36 + 5 (range 30 + 5 to 40 + 6 weeks). The mean time interval from birth to neonatal manifestations of infection was 5.2 (0–9) days. The most common presenting sign in the neonates was fever ( n  = 8, 61.5%). All neonates required the neonatal intensive care unit. The neonatal mortality rate was 3/13 (23%). Conclusion: The neonatal morbidity and mortality from the enterovirus infection may have been associated with the severity of maternal presentation at the time of admission. Enterovirus real‐time polymerase chain reaction analysis should be considered as part of the maternal evaluation in cases of maternal fever of unknown origin. Deferral of the induction of delivery for term pregnancies with confirmed enterovirus infections should be considered.